2022
DOI: 10.1039/d2fo00943a
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of one-carbon metabolism-related nutrients and hepatocellular carcinoma survival in the Guangdong Liver Cancer Cohort

Abstract: Dietary intake of one-carbon metabolism-related nutrients has been linked to cancer-related outcomes, but their effects on hepatocellular carcinoma (HCC) mortality are still unknown. The objective was to assess whether pre-diagnostic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Six studies (four case-control and two cohort studies) addressed the association between vitamin B12 (plasma concentration and/or intake) and hepatic cancer or mortality after the diagnosis of hepatic cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. The exposure in five of those studies was serum/plasma B12, while one study additionally investigated vitamin B12 intake [ 7 ] and one study investigated only vitamin B12 intake [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies (four case-control and two cohort studies) addressed the association between vitamin B12 (plasma concentration and/or intake) and hepatic cancer or mortality after the diagnosis of hepatic cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. The exposure in five of those studies was serum/plasma B12, while one study additionally investigated vitamin B12 intake [ 7 ] and one study investigated only vitamin B12 intake [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (four case-control and two cohort studies) addressed the association between vitamin B12 (plasma concentration and/or intake) and hepatic cancer or mortality after the diagnosis of hepatic cancer [ 7 , 8 , 9 , 10 , 11 , 12 ]. The exposure in five of those studies was serum/plasma B12, while one study additionally investigated vitamin B12 intake [ 7 ] and one study investigated only vitamin B12 intake [ 12 ]. The reference categories of plasma B12 concentrations in the individual studies were based on the within-study data distribution and showed large variations between the studies (i.e., reference categories of plasma B12 were <699 ng/L (or 516 pmol/L); 227–265 pmol/L; <154 pmol/L; and 200–600 pmol/L).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shotgun proteomics analysis indicated a significant decrease of methionine metabolism enzymes (MAT1A, GNMT, and AHCY) and trans-sulfuration pathway enzyme (CBS) after PH (Figure 6B). Since OCM is essential in maintaining quiescent and differentiated hepatocytes, [43][44][45][46] and its regulation during LR is poorly understood, we have performed a systematic analysis of 12 enzymes involved in this pathway. To this end we used a standardized PRM assay targeting enzymes catalyzing reactions of the methionine cycle (MAT1A, MAT2A, MAT2B, GNMT, AHCY, BHMT, and MTAP), the folate cycle (SHMT1 and 2, DHFR), and the transsulfuration pathways (CTH and CBS).…”
Section: Inhibition Of Ocm At 9 H Upon Ph In Micementioning
confidence: 99%